FRI0061 THE ADVERSE OBSTETRIC OUTCOMES WHEN RHEUMATOID ARTHRITIS IS CONTROLLED DURING PREGNANCY: IS THE DISEASE ITSELF A PROBLEM? DATA FROM A CASE-CONTROL COHORT OF 190 PREGNANCIES AT A MULTI-NATIONALITY SPECIALIZED CENTER IN QATAR. (2nd June 2020) - Elsayed, E.; Abuyaqoub, S.; Almallahi, N.; Alam, F.; Saleh, R.; Chandra, P.; Almulla, N.; Al Kahlout, M.; Hamed, M.; Abdulla, N.; Al Emadi, S.
Abstract : Background: Rheumatoid arthritis is implicated in causing adverse pregnancy outcomes including high rates of prematurity and low birth weight. But little is known about the impact of the disease when it's controlled as most of the information is extracted from retrospective data. Objectives: To examine the adverse obstetric outcomes after controlling disease during pregnancy. We also took into account many confounders that might affect the outcome. Methods: This is an ongoing Case-Control Prospective Cohort. It is implemented in a tertiary center where cases are recruited from a single specialized pregnancy and rheumatic disease clinic to ensure standardized management. These cases were fulfilling the ACR 2010 classification criteria for rheumatoid arthritis. Disease activity was measured using CDAI once before pregnancy and once in each trimester. We excluded subjects with chronic morbidities or twin pregnancy. Data were collected in pre-specified data sheets. Routine blood tests in addition to C-reactive protein were obtained. Cases were recruited at different disease activity stages, but treatment was escalated to reach remission as possible by the third trimester. Data were analyzed using SPSS software for descriptive and comparative analyses. Results: Since 2017 we have recruited 215 subjects. A total of 190 completed pregnancies were analyzed in this report (114 controls and 76 cases). Five subjects were excluded as their disease was not controlled by 27 weeks of gestation. Baseline characteristics of age, baseline BMI and anemia were similar. Exposure to passive smoking was significantly higher in the control group. There was no statistical difference in the incidence of gestational diabetes, pre-eclampsia and infections. Rates of abortions and cesarean sections were significantly higher in the cases group. The incidence of PROM & low birth weight was not statistically different. Three cases of IUFD were reported among controls versus none in the cases (Table 1 ). Prematurity rate was numerically higher in the control group but did not reach a statistical difference. Congenital anomalies and NICU admission rates were comparable between the groups. But the incidence of neonatal morbidities was significantly higher in the control group (p. value 0.006), but the majority of morbidities were due to jaundice that resolved with phototherapy. we have evaluated the incidence of group B streptococcal Agalactae as a possible contributor to morbidities but it was similar between the groups. All cases were on DMARDs during pregnancy. Hydroxychloroquine was the most commonly used (55%) followed by sulfasalazine (40%). Steroid was used for variable duration in pregnancy in 23 cases. In most of them, it was tapered and stopped by the end of pregnancy. Biologics were used in 15 cases with few adverse outcomes including: abortion (1 case), PROM (1), maternal UTI (1), repeated URT infection (1) and neonatal bronchiolitis (1). Conclusion: From this ongoing cohort we conclude that controlled RA during pregnancy carries low risk of adverse obstetric outcomes in spite the regular use of DMARDs. Although these results are reassuring, further regression models are required after recruiting more subjects. References: [1]Johanna M. W. Hazes. (2011). Rheumatoid arthritis and pregnancy: evolution of disease activity and pathophysiological considerations for drug use. Rheumatology, 50:1955-1968 Disclosure of Interests: None declared